Prevalence and Sensitivity Pattern of Gram-negative Bacilli Multidrug-Resistant (MDR) In Mohammad Hoesin Hospital Palembang - Vena Sabputri Sutrisno; Mastiar Endang Frida Siahaan; Desi Oktariana; Phey Liana; Lusia Hayati (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2022)
Antibiotic resistance is one of the most serious global health crisis and threats in human life today. Multidrug-resistant is a condition obtained when bacteria are resistant to at least one of the agents of 3 or more antimicrobial categories. Cases of multi-resistant gram-negative bacilli infection continue to increase so that the use of standard antibiotics is non-susceptible leading to increased morbidity and mortality. Therefore, this study aims to find out which antibiotics are still sensitive as empirical therapy. This retrospective descriptive research uses secondary data in the form of the status of patients infected with A. baumannii, P. aeruginosa, E. coli and K. pneumoniae at the Central Laboratory Installation of Mohammad Hoesin Hospital Palembang during the period January 2020 – June 2020. The samples in this study were all medical records of inpatients who met the inclusion criteria. Data is processed and analyzed univariately using Microsoft Excel 2020 and IBM SPSS Statistics Version 26 to determine the frequency distribution of each variable studied. Prevalence of MDR gram-negative bacilli at Mohammad Hoesin Hospital Palembang was MDR A. baumannii (66.5%), MDR P. aeruginosa (34.6%), ESBL-E. coli (61.3%), CRE-E. coli (2.7%), ESBL-K. pneumoniae (51.7%) and CRE-K. pneumoniae (20.1%). Based on the inpatient room, prevalence of MDR gram-negative bacilli is found in intensive care compared to non-intensive care rooms. Based on specimen type, MDR gram-negative bacilli isolates are often found in all types of specimens namely sputum, blood, pus, swab, others. Based on sensitivity patterns, Enterobacteriaceae producing ESBL isolates are sensitive to carbapenem, amikacin, tigecyclin and nitrofurantoin, while in CRE isolates are sensitive to tigecycline. MDR A. baumannii is sensitive to tigecycline and amikacin, but MDR P. aeruginosa is only sensitive to amikacin. The prevalence of MDR gram-negative bacilli is the highest in the intensive inpatient rooms and varies in specimen type. Antibiotics that are sensitive to the entire MDR gram negative bacilli is tigecycline, except MDR P. aeruginosa is sensitive to amikacin.